The Waqf Bank and Social Responsibility: A Proposed Framework for Application in the Jordanian Economy - Abusweilem, Mu'minah Musa Omir; Al-Hourani, Yasser Abdel Karim; Ubeidat, Ziad Mohammed Mehmud (Journal of Islamic and Religious Studies, 2025)
This study explores the concept and practical implementation of a Waqf bank as a contemporary financial institution grounded in Islamic principles. Rooted in the charitable spirit of Islamic Waqf (endowment), the proposed Waqf bank addresses the challenge of managing small, scattered endowments by integrating them into a structured financial entity. The bank is designed to uphold the objectives of Waqf donors, operate under established banking systems, and serve various aspects of social responsibility. The research aims to define the concept, objectives, operational structure, and governance of the Waqf bank, while also examining its potential contributions to the Jordanian economy and its alignment with social responsibility goals. The study utilizes an analytical approach and concludes that the primary financial resources for the Waqf bank include zakat, charitable donations, benevolent (qard hasan) loans, customer accounts, and a portion of the bank's profits. The bank’s funds are strategically divided: one part for charitable financing—offering interest-free loans for education, healthcare, marriage, and seasonal needs—and another for economically viable investments to ensure sustainability and institutional growth. A key finding emphasizes the necessity of a comprehensive Shariah supervisory system, which reinforces the bank’s dual nature as both an Islamic financial institution and a Waqf entity. This oversight fosters trust among stakeholders and ensures compliance with Islamic ethics. The study recommends promoting the investment of Waqf assets through dedicated Waqf banks, highlighting their role in financial sustainability, community development, and effective Sharia-compliant governance. The model presents an innovative bridge between Islamic heritage and modern financial needs.